Aiming for the future: CEO future focus and corporate social performance - Seunghye Lee; Dokyun Kwon; Yangmin Kim (Global Business & Finance Review (GBFR), 2023)
Purpose: This study aims to investigate whether CEO future focus leads to improvements in the CSP. Although there has been extensive research on the antecedents of CSP, little has addressed the role of CEOs' subjective biases in determining how future time frames affect CSP. This study fills this gap by adopting the concept of CEO future focus and examines the relationship between CEO future focus and CSP. Design/methodology/approach: The sample of this study includes 933 (firm-year) observations from 178 publicly traded U.S. manufacturing firms between 2005 and 2011. This study conducts generalized estimating equations (GEE) model to test our hypotheses. Findings: The finding shows that a CEO's future focus is positively related to CSP. Given the long-term orientation of CSP, this result shows that a CEO with a strong future focus is more likely t o be l ooking ahead a t possible future gains by enhancing CSP. The results also show that various boundary conditions shape the positive relationship between CEO future focus and CSP. Specifically, this study finds that the positive relationship between CEO future focus and CSP is weakened when a CEO has longer tenure, when a CEO has a higher proportion of fixed pay in his/her pay packages, and when an organization confronts a shifting and challenging external environment. Research limitations/implications: This study extends both the strategic leadership and CSR literature in that a CEO's temporal foci, especially future focus, influence corporate social activities. However, this study has limitation related to the measurement of future focus. In addition, this study only considers CEO future focus rather than the past and present focus. Originality/value: This study extends the study of CEO characteristics by investigating how micro-foundations, in the form of CEO future focus, affect CSP. The study provides more in-depth understanding of CEO characteristics by adopting the concept of future focus and examine its impact on the CSP. In addition, the study provides a more precise understanding of the relationship between CEO future focus and CSP by investigating various boundary conditions such as CEO and industry characteristics.
Keywords: 650; CEO future temporal focus; Corporate social performance; CEO tenure; CEO pay structures; Industry dynamism